PROFESSOR EMERITUS OF THE KYIV UNIVERSITY, TOLSTOY MYKHAYLO – GEOLOGIST-GEOPHYSICIST - Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article describes the scientific, pedagogical and management activities of the prominent Ukrainian scientist, organizer of the scientific structure of the Kiev University, the famous geologist-geophysicist – Professor Emeritus Tolstoy Mykhailo. The evolution from the scientistpragmatist to the founder of the interbranch scientific school is covered. There are the stages of foundation, development and solving of a number of fundamental problems of geology: the quantitative analysis of the distribution of chemical elements and physical properties of magmatic formations using mathematical methods, paleogeodynamic and metallogenic prediction based on the analysis of complex data, geophysics of landscapes; numerous heritage of applied developments – an unique databases of geological data of intrusive and volcanogenic rocks, lithotheque, a fund of standards, the monitoring sites etc.